"Are We Talking About the Same Person Here?": Interrater Agreement in Judgments of Personality Varies Dramatically With How Much the Perceivers Like the Targets. (July 2013) - Leising, Daniel; Ostrovski, Olga; Zimmermann, Johannes
We investigated how interrater agreement in personality judgment is affected by the perceivers' affection or dislike regarding the targets. A total of 209 perceivers judged the personalities of 15 targets by means of 30 adjectives. The targets were public figures (e.g., the Pope), which enabled gathering a large number of ratings by perceivers differing in liking. Shared liking was associated with strong increases, and large liking differences were associated with strong decreases, in profile correlations. Shared antipathy was also associated with lower agreement. The greater agreement between judgments of liked targets was largely due to the perceivers characterizing targets positively, whereas judgments of disliked targets were not affected by (shared) negativity to the same extent. The perceivers' attitudes toward the targets constitute an important factor in person perception and need to be taken into account more systematically in research studies.